The encouraging factors of breastfeeding among women academicians in Malaysian higher education institution of Kuala Terengganu, Malaysia - Normadiah, Daud; Che Suhaili, Che Taha; Nadhirah, Nordin; Norsuhaily, Abu Bakar; Zurita, Mohd.Yusoff (2015)
Breast milk is babies' best food. It contains balance nutritions to help save babies from diseases. However, the busy life of a career woman foils the desire to provide for full lactation. Therefore, this study was conducted to identify the encouraging factors for breastfeeding among women academicians in conjunction to apply these factors to all career women in general. The study was carried out by the method of quantitative and field studies strategy. Data were collected through questionnaires and interviews by experts in each particular field. A total of 140 out of 180 respondents were selected from a number of selected Malaysian Higher Education Institution in the locality of Kuala Terengganu, i.e., MARA University of Technology (UiTM) Kuala Terengganu, University of Malaysia Terengganu (UMT) and University of Sultan Zainal Abidin (UniSZA). Data obtained were analyzed using the software Statistical Package for the Social Sciences (SPSS). The results showed that the respondents had a variety of encouraging factors involving the self factor of nursing mother, the husband, the infant child and the mother's milk factor. However, the most popular encouraging factor for breastfeeding among the respondents among others was the mother's milk factor due to the wondrous efficacy of colostrum in the milk content with a mean of 3.91 (140 respondents). These findings proved that knowledge plays, an important role in the success of any implementation issue (face to face) the implementation of breastfeeding among nursing mothers.